第54次日本南極地域観測隊と2012-2013年ベルギー南極観測隊との合同によるナンセン氷原における隕石探査報告 - 今栄, 直也; イマエ, ナオヤ; Debaille, Vinciane; 赤田, 幸久; アカダ, ユキヒサ; Debouge, Wendy; Goderis , Steven; Hublet, Genevieve; 三河内, 岳; ミコウチ, タカシ; Van Roosbroek, Nadia; 山口, 亮; et al. (2015)
P(論文) 第54次日本南極地域観測隊員4名とベルギー南極観測隊員6 名の合計10名から構成される隕石探査隊は，2012年12月から2013年2月まで，セール・ロンダーネ山地南部に広がるナンセン氷原（南緯72°30′-73°，東経23°-25°，標高約2900-3000m）において隕石探査を実施した．ナンセン氷原には2012年12月26日から2013年2月2日まで39日間滞在した．今回の探査域は第29次日本南極地域観測隊以降探査が行われていない．探査の結果，採集した隕石の総数は424個，合計重量は約70kgであった．隕石発見地点は携帯GPSに記録されたので，探査域における隕石の分布が明確になった．これは隕石集積機構解明のための基礎データだけでなく，今後の探査計画に活用できる．本稿は主に日本隊による準備期間を含む実施報告書である． This paper reports on a joint expedition (JARE-54 and BELARE 2012-2013) that conducted a search for meteorites on the Nansen Ice Field, Antarctica, in an area south of the Sor Rondane Mountains (72°30′-73°S, 23°-25°E; elevation 2900-3000 m). The expedition took place over a period of 39 days during the austral summer, between 26 December 2012 and 2 February 2013. The team consisted of ten members: three researchers and one field assistant from the 54th Japanese Antarctic Research Expedition (JARE-54), and five researchers and one field assistant from the Belgian Antarctic Expedition (BELARE) 2012-2013. Previously, this area had only been searched by JARE-29. The team collected 424 meteorites, which had a total weight of about 70 kg. The search tracks of the ten members of the expedition were recorded using hand-held GPS units, and this allowed the distribution of meteorites within the searched area to be mapped. The resultant data will be useful for planning future expeditions and can be used to clarify the meteorite concentration mechanism on the ice field. This paper focuses on the activities of JARE-54 during the joint expedition. departmental bulletin paper